Unexpected population response to increasing temperature in the context of a strong species interaction. Issue 5 (19th June 2017) - White, Jeffrey D.; Sarnelle, Orlando; Hamilton, Stephen K.
Abstract: Climate change is driving large changes in the spatial and temporal distributions of species, with significant consequences for individual populations. Community‐ and ecosystem‐level implications of altered species distributions may be complex and challenging to anticipate due to the cascading effects of disrupted interactions among species, which may exhibit threshold responses to extreme climatic events. Toxic, bloom‐forming cyanobacteria like Microcystis are expected to increase worldwide with climate change, due in part to their high temperature optima for growth. In addition, invasive zebra mussels ( Dreissena polymorpha ) have caused an increase in Microcystis aeruginosa, a species typically associated with eutrophication, in low‐nutrient lakes. We conducted a 13‐yr study of a M. aeruginosa population in a low‐nutrient lake invaded by zebra mussels. In 10 of the 13 years, there was a significant positive relationship between M. aeruginosa biomass and accumulated degree days, which are projected to increase with climate change. In contrast, Microcystis biomass was up to an order of magnitude lower than predicted by the above relationship during the other three years, including the warmest in the data set, following repeated heat‐induced mass mortality of D. polymorpha . Thus, the positive relationship between Microcystis biomass and temperature was negated when its facilitating species was suppressed during a series of exceptionally warm summers. Predicting the net response of a species to climate change may therefore require, at minimum, quantification of responses of both the focal species and species that strongly interact with it over sufficiently long time periods to encompass the full range of climatic variability. Our results could not have been predicted from existing data on the short‐term responses of these two interacting species to increased temperature.